Social learning and culture in child and chimpanzee. [article]. - Whiten, Andrew
A few decades ago, we knew next to nothing about the behavior of our closest animal relative, the chimpanzee, but long-term field studies have since revealed an undreamed-of richness in the diversity of their cultural traditions across Africa. These discoveries have been complemented by a substantial suite of experimental studies, now bridging to the wild through field experiments. These field and experimental studies, particularly those in which direct chimpanzee?child comparisons have been made, delineate a growing set of commonalities between the phenomena of social learning and culture in the lives of chimpanzees and humans. These commonalities in social learning inform our understanding of the evolutionary roots of the cultural propensities the species share. At the same time, such comparisons throw into clearer relief the unique features of the distinctive human capacity for cumulative cultural evolution, and new research has begun to probe the key psychological attributes that may explain it. -- (from the author)